Proceedings of the 2nd International Conference on Civil, Materials and Environmental Sciences 2015
DOI: 10.2991/cmes-15.2015.185
|View full text |Cite
|
Sign up to set email alerts
|

NaCl Effect on SOFC Cathode

Abstract: Abstract-The fact that NaCl in air has induced degradation of cathode has been investigated for La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3 (LSCF). Cell performance was measured by volatilizing NaCl into the air supplied to the cathode at a constant current density of 200 mA cm -2 up to 100 h. At 800 o C, an exposure to 30 ppm NaCl caused negligible degradation of LSCF cathode at least for 100 h, yet degradation became obvious with increasing NaCl concentration. Slight change in the composition of the cathode materials wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 8 publications
1
3
1
Order By: Relevance
“…The results of the short-term tests are qualitatively similar to those obtained by Liu et al [3], but in contrast to them we did find more reduction in cell performance, although still moderate, with the higher salt concentration in the cathode feed than with the lower concentration.…”
Section: Pt B-k C-k O-k Na-k Al-k Ca-k Sc-k Mn-k Ni-k Sr-l Zr-lsupporting
confidence: 89%
See 4 more Smart Citations
“…The results of the short-term tests are qualitatively similar to those obtained by Liu et al [3], but in contrast to them we did find more reduction in cell performance, although still moderate, with the higher salt concentration in the cathode feed than with the lower concentration.…”
Section: Pt B-k C-k O-k Na-k Al-k Ca-k Sc-k Mn-k Ni-k Sr-l Zr-lsupporting
confidence: 89%
“…Liu et al [3] did not perform long-term tests and could therefore not have found the same severe reduction in cell performance due to delamination as we found in this study.…”
Section: Long-term Salt Degradation Testscontrasting
confidence: 63%
See 3 more Smart Citations